Gottfried von Strassburg - A German Humanist of the Twelfth Century Par Excellence - Albrecht Classen, (Futhark. Revista de Investigación y Cultura, 2021)
Normally we identify the so-called Renaissance of the twelfth centuty with theologians, philosophers, and artists. But many poets from the turn of the century (1200) have made major intellectual contributions to this Renaissance as well. Especially Gottfried von Strassburg’s Tristan can be regarded as an extraordinary literary accomplishment characterized by its fascinating combination of fictional elements with those of a philosophical origin. The purpose of this article is to recognize the central message of Tristan as not being limited to the theme of love, but, emerging from the discourse of love, as a critical engagement with basic question pertaining to human existence.